2021
DOI: 10.1007/jhep04(2021)149
|View full text |Cite
|
Sign up to set email alerts
|

Towards a complete mass spectrum of type-IIB flux vacua at large complex structure

Abstract: The large number of moduli fields arising in a generic string theory compactification makes a complete computation of the low energy effective theory infeasible. A common strategy to solve this problem is to consider Calabi-Yau manifolds with discrete symmetries, which effectively reduce the number of moduli and make the computation of the truncated Effective Field Theory possible. In this approach, however, the couplings (e.g., the masses) of the truncated fields are left undetermined. In the present paper we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 129 publications
(348 reference statements)
2
19
0
Order By: Relevance
“…In our scheme, the mass spectrum clearly depends on the correction K (3) , as one of the fields is only stabilised when they are taken into account. This is also consistent with the results of [45,48], since the parameter ξ that controls their mass spectrum is a simple function of K (3) . Furthermore, we also showed that in one particular case in which the matrix M is not invertible, we recover the residual flat direction found in [47] for the same flux choices.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our scheme, the mass spectrum clearly depends on the correction K (3) , as one of the fields is only stabilised when they are taken into account. This is also consistent with the results of [45,48], since the parameter ξ that controls their mass spectrum is a simple function of K (3) . Furthermore, we also showed that in one particular case in which the matrix M is not invertible, we recover the residual flat direction found in [47] for the same flux choices.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis presented in this paper offers some avenues to follow in the future: first of all it would be interesting to calculate the precise mass spectra for the F-theory vacua obtained here as done in [45,48] for the type IIB case. In this way one could verify whether there is indeed a hierarchy between the masses of the fields in the complex structure sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our scheme, the mass spectrum clearly depends on the correction K (3) , as one of the fields is only stabilised when they are taken into account. This is also consistent with the results of [41,43], since the parameter ξ that controls their mass spectrum is a simple function of K (3) . Furthermore, we also showed that in one particular case in which the matrix M is not invertible, we recover the residual flat direction found in [42] for the same flux choices.…”
Section: Discussionsupporting
confidence: 91%
“…• The distribution of the string coupling g s is taken to be uniform. This result was explicitly checked in [5] for rigid CY manifolds and is believed to hold for more general cases as well [53]. Hence in the following we shall take dN dg s where N is the number of flux vacua.…”
Section: Jhep08(2021)059 3 Statistics Of Axion Physics In the Flux Landscapementioning
confidence: 73%